Adherence to rivaroxaban for the treatment of venous thromboembolism–Results from the FIRST registry. Issue 8 (21st November 2021) - Speed, Victoria; Auyeung, Vivian; Patel, Jignesh P.; Cooper, Derek; Miller, Stephen; Roberts, Lara N.; Patel, Raj K.; Arya, Roopen
Abstract: Background: Medication nonadherence can result in poor clinical outcomes and significant costs to health care providers. When treating venous thromboembolism (VTE), subtherapeutic anticoagulation may contribute to complications such as recurrent VTE or postthrombotic syndrome. Objectives: To describe the extent, reasons for, and predictors of nonadherence to rivaroxaban for the treatment of VTE in clinical practice in the United Kingdom reported by participants of the FIRST registry. Patients/Methods: The FIRST registry was an observational, multicenter registry reporting on the use of rivaroxaban in routine clinical practice. FIRST registry participants completed an adherence screening questionnaire during their treatment and follow‐up. Results: In total, 1028 participants completed 1660 questionnaires over 2 years. One hundred thirteen of 1028 (11%) reported nonadherence at 28 days (interquartile range, 21‐45). Reasons given for nonadherence at 1 month were forgetfulness (8.6% vs 74.7%; P  < .001), carelessness (2.7% vs 27.3%; P  < .001) or a change in routine (7.4% vs 25.5%; P  < .001) reported by adherent and nonadherent participants, respectively. Older age (10‐year increments) was the strongest predictor of good adherence (adjusted odds ratio, 1.21; 95% confidence interval, 1.06‐1.39; 1 = adherent). Conclusions: Overall adherence to rivaroxaban was high, and most nonadherence was unintentional. Identification of those at risk of nonadherence may reduce the risk of VTE recurrence and long‐term complications.